A composite carbon cloth electrode suitable for flow-through flow battery and its preparation method and application

CN122889774APending Publication Date: 2026-10-09YULIN SHENHUA ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610977153.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

在流过式液流电池中,双极板具有复杂的流道结构,碳布材料放置于双极板上时,因其过于柔软而易塌陷至流道底部,从而脱离与膜的接触,导致电池欧姆内阻增大、工作电流在电极上非均匀分布等问题,从而导致电池性能下降,电极使用寿命缩短

Benefits of technology

[0023]与现有技术相比,本发明技术方案的有益效果至少在于:通过在碳布编织过程中添加金属丝并且碳纤维丝与金属丝的数量比例在合适范围,可使复合碳布电极材料有较高的硬挺度,组装流过式液流电池电堆时,碳布不易塌陷至双极板流道中,使碳布电极与膜能均匀接触,提供更多的反应场所,所得该复合碳布电极用于液流电池时能够提高电极寿命和液流电池的能量效率;另外,采用本发明的制备方法,在提高碳布硬挺度的条件下,减少金属丝的用量,节约成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of carbon cloth electrode preparation, and particularly relates to a composite carbon cloth electrode suitable for flow-through liquid flow battery and a preparation method and application thereof; the method comprises the following steps: (1) twisting pre-oxidized carbon fibers to obtain pure carbon fiber yarn; twisting the pre-oxidized carbon fibers and metal wires to obtain mixed yarn; (2) manufacturing carbon fiber cloth on a loom, wherein the mixed yarn is used in the longitudinal direction, and the pure carbon fiber yarn is used in the transverse direction; or the mixed yarn is used in the transverse direction, and the pure carbon fiber yarn is used in the longitudinal direction; or the mixed yarn is used in both directions; (3) performing carbonization treatment on the obtained carbon fiber cloth; (4) performing plasma treatment on the surface of the carbonized carbon cloth, and then performing immersion treatment in acid liquor to obtain the composite carbon cloth electrode. The composite carbon cloth electrode of the application is not easy to collapse into the flow channel of the bipolar plate, can uniformly contact the membrane, provides more reaction sites, and finally improves the energy efficiency of the liquid flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon cloth electrode preparation technology, and particularly relates to a composite carbon cloth electrode suitable for flow batteries, its preparation method and application. Background Technology

[0002] Flow batteries are a large-scale electrochemical energy storage technology. Compared with other energy storage technologies, they have advantages such as high energy conversion efficiency, flexible system design, large energy storage capacity, free site selection, deep discharge capability, safety and environmental protection, and low maintenance costs. They can be widely used in renewable energy power generation and storage, emergency power systems, backup power stations, and peak shaving and valley filling of power systems.

[0003] Electrode materials are one of the key components of flow batteries, and their conductivity, porosity and pore structure, electrochemical catalytic activity, and mechanical properties affect the battery's operating current density and energy efficiency. Currently, the electrode materials commonly used in all-vanadium redox flow batteries are carbon cloth, carbon paper, or carbon felt.

[0004] For example, patent document CN102704227A discloses a method for preparing polyacrylonitrile carbon cloth material: using polyacrylonitrile-based pre-oxidized fiber as raw material to weave cloth; sending the polyacrylonitrile-based pre-oxidized fiber cloth to a carbonization furnace for heating and carbonization; washing with water and then sending it to a dryer for drying to obtain polyacrylonitrile carbon cloth material.

[0005] The carbon cloth material prepared by existing technology appears soft. In flow batteries, the bipolar plates have a complex flow channel structure. When the carbon cloth material is placed on the bipolar plates, it is too soft and easily collapses to the bottom of the flow channel, thus losing contact with the membrane. This leads to problems such as increased ohmic internal resistance of the battery and non-uniform distribution of operating current on the electrodes, resulting in decreased battery performance and shortened electrode life.

[0006] Therefore, how to prepare carbon cloth electrodes with a certain degree of hardness so that the carbon cloth does not easily collapse into the bipolar plate channel so that it can make uniform contact with the film is a direction worthy of further research. Summary of the Invention

[0007] The purpose of this invention is to address some shortcomings of existing carbon cloth electrodes by providing a composite carbon cloth electrode suitable for flow batteries, its preparation method, and its application. By adding metal wires during the carbon cloth weaving process, the composite carbon cloth electrode material can achieve higher hardness. When assembling a flow battery stack, the composite carbon cloth is less likely to collapse into the bipolar plate channel, allowing the carbon cloth electrode to make uniform contact with the membrane, providing more reaction sites, and ultimately improving the energy efficiency of the flow battery.

[0008] To achieve the above objectives, the present invention provides the following technical solution: In the first aspect, a method for preparing a composite carbon cloth electrode suitable for a flow battery is provided, comprising: (1) Twist the pre-oxidized carbon fiber to obtain the twisted pure carbon fiber yarn; twist the pre-oxidized carbon fiber and metal wire to obtain the twisted mixed yarn; (2) Make carbon fiber cloth on a loom (the length, width and thickness range of the carbon fiber cloth are mainly determined by the size of the battery and do not directly affect the performance of the electrode and the battery). The longitudinal direction uses the mixed yarn after twisting in step (1), and the transverse direction uses the pure carbon fiber yarn after twisting in step (1); or, the transverse direction uses the mixed yarn after twisting in step (1), and the longitudinal direction uses the pure carbon fiber yarn after twisting in step (1); or, both the longitudinal and transverse directions use the mixed yarn after twisting in step (1). (3) Carbonize the carbon fiber cloth obtained in step (2) to obtain carbonized carbon cloth. (4) The carbon cloth surface obtained above is subjected to plasma treatment to obtain a surface-modified carbon cloth electrode; (5) The plasma-treated carbon cloth electrode is immersed in acid solution to obtain a composite carbon cloth electrode (with certain support, high conductivity and hydrophilicity).

[0009] According to the preparation method provided by the present invention, in some embodiments, the pre-oxidized carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber, and pitch-based carbon fiber.

[0010] In some embodiments, the pre-oxidized carbon fiber has a diameter of 5 to 20 μm, for example, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, or 18 μm.

[0011] In some embodiments, the metal wire is selected from one or more of copper wire, iron wire, platinum wire, titanium wire, tungsten wire, and iridium wire.

[0012] In some embodiments, the diameter of the metal wire is 5~200μm, for example, 6μm, 10μm, 15μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 120μm, 150μm, 180μm.

[0013] According to the preparation method provided by the present invention, in some embodiments, the number of pre-oxidized carbon fiber monofilaments in the twisted pure carbon fiber yarn is 10 to 200, for example, 12, 15, 20, 25, 30, 40, 50, 60, 80, 100, 120, 150, or 180.

[0014] In some implementations, the ratio of the number of pre-oxidized carbon fiber monofilaments to the number of metal wires in the twisted blended yarn is 8:1 to 12:1, preferably 10:1.

[0015] In some implementations, the carbonization process conditions in step (3) include: under inert gas protection, the system is heated to 500~1400℃ (e.g., 600℃, 800℃, 1000℃, 1200℃, 1300℃) for carbonization, and the processing time is 2~4h (e.g., 2.5h, 3h, 3.5h).

[0016] In some implementations, the carbonized carbon cloth is further washed and dried before plasma treatment. The washing and drying process is as follows: the carbonized carbon cloth is cooled and removed, then soaked in boiling water for 3-5 times, each time for 30 minutes, to remove tar impurities on the surface, and then dried with nitrogen hot air at 80-120°C (e.g., 90°C, 100°C, 110°C) for 2-4 hours (e.g., 2.5 hours, 3 hours, 3.5 hours).

[0017] In some implementations, the process conditions for plasma treatment in step (4) include: treating the surface of carbon cloth with 200-500W (e.g., 300W, 400W) plasma in an air atmosphere for 5-30 minutes (e.g., 6 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes).

[0018] The carbon cloth is modified by plasma treatment, which forms oxygen-containing functional groups (-COOH, -OH, etc.) on the surface of the carbon cloth electrode.

[0019] In some implementations, the process of step (5) of soaking in acid solution includes: soaking in dilute acid solution at room temperature for 1 to 24 hours (e.g., 2 hours, 4 hours, 5 hours, 10 hours, 12 hours, 15 hours, 20 hours), washing with water until neutral, and purging with nitrogen to dry, to obtain composite carbon cloth electrode.

[0020] In some embodiments, the dilute acid solution is a dilute sulfuric acid solution with a concentration of 0.1~0.5 mol / L, for example, 0.2 mol / L, 0.3 mol / L, or 0.4 mol / L.

[0021] In a second aspect, a composite carbon cloth electrode prepared by the method described above is provided.

[0022] In a third aspect, the application of a composite carbon cloth electrode prepared by the method described above in a flow battery is provided.

[0023] Compared with the prior art, the beneficial effects of the technical solution of the present invention are at least as follows: by adding metal wires during the carbon cloth weaving process and ensuring that the ratio of carbon fiber wires to metal wires is within a suitable range, the composite carbon cloth electrode material can have high stiffness. When assembling a flow battery stack, the carbon cloth is less likely to collapse into the bipolar plate channel, allowing the carbon cloth electrode to contact the membrane evenly and providing more reaction sites. The resulting composite carbon cloth electrode can improve electrode life and energy efficiency of the flow battery when used in a flow battery. In addition, by using the preparation method of the present invention, the amount of metal wires used is reduced while increasing the stiffness of the carbon cloth, thus saving costs. Detailed Implementation

[0024] To provide a detailed understanding of the technical features and content of this invention, preferred embodiments will be described in more detail below. While preferred embodiments of the invention are described in the examples, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0025] This article describes a method for preparing a composite carbon cloth electrode suitable for flow batteries, comprising: 1) Select pre-oxidized carbon fiber and metal wire as raw materials. The pre-oxidized carbon fiber can be, but is not limited to, polyacrylonitrile-based pre-oxidized carbon fiber, viscose-based pre-oxidized carbon fiber, pitch-based pre-oxidized carbon fiber, etc., with a diameter of 5~20μm; the metal wire can be, but is not limited to, copper wire, iron wire, platinum wire, titanium wire, tungsten wire, iridium wire, etc., with a diameter of 5~200μm. The oxygen content of the pre-oxidized carbon fiber precursor is controlled at 6-10% (e.g., 7%, 8%, 9%) and the elongation at break is 12-18% (e.g., 13%, 15%, 16%) to meet the twisting conditions. Selected pre-oxidized carbon fibers are twisted into pure carbon fiber yarn; and selected pre-oxidized carbon fibers and metal wires are twisted into a blended yarn with a specific monofilament content. In this step, the twisting operation can be a conventional method in the field. For example, the twisting operation can be completed with a target twist of 200-400 twists / meter and a twist direction of Z, so that the loose monofilament bundle can be formed into a tightly structured yarn. In pure carbon fiber yarn, the number of pre-oxidized carbon fiber monofilaments is 10 to 200. In blended yarns, the ratio of pre-oxidized carbon fiber monofilaments to metal wires can be from 8:1 to 12:1, for example, 10:1.

[0026] 2) Produce carbon fiber cloth of fixed width, length, and thickness on a loom (the length, width, and thickness range of the carbon fiber cloth are mainly determined by the size of the battery and do not directly affect the electrode and battery performance). In this case, the longitudinal direction uses a mixed yarn of pre-oxidized carbon fiber and metal wire obtained by twisting, and the transverse direction uses pure carbon fiber yarn obtained by twisting; or, the transverse direction uses a mixed yarn of pre-oxidized carbon fiber and metal wire obtained by twisting, and the longitudinal direction uses pure carbon fiber yarn obtained by twisting; or, both the transverse and longitudinal directions use a mixed yarn of pre-oxidized carbon fiber and metal wire obtained by twisting. In this step, the fabric on the machine is woven with single strands of yarn; and the weaving texture can be plain weave / twill / herringbone, etc.; the weaving warp and weft density is: 12-18 warp threads / cm, 12-18 weft threads / cm; the fabric is a single layer. 3) Place the carbon fiber cloth woven by the loom in a sealed carbonization furnace, and continuously heat it to 500~1400℃ under inert gas protection, and keep it at a constant temperature for 2~4 hours; 4) Cool down and remove the carbon cloth. Soak it in deionized water and boiling water three times, 30 minutes each time, to remove surface tar impurities. Dry it with nitrogen hot air (temperature 80-120℃, time 2-4 hours). 5) In an air atmosphere, the surface of the washed and dried carbon cloth electrode is treated with 300W plasma for 5 to 30 minutes to form oxygen-containing functional groups such as -COOH and -OH on the electrode surface. 6) The surface-modified carbon cloth electrode is immersed in dilute sulfuric acid solution (concentration of 0.1~0.5mol / L) at room temperature for 1~24h, washed with deionized water until neutral, and dried by nitrogen purging to finally obtain a composite carbon cloth electrode with certain support, high conductivity and hydrophilicity.

[0027] This invention twists selected pre-oxidized carbon fibers and metal wires into yarns with a specific monofilament content and controls the ratio of carbon fiber filaments to metal wires in the yarn. Furthermore, during the weaving process, a mixed yarn of pre-oxidized carbon fiber and metal wire is used in one direction. This layout and design can reduce the amount of metal wire used while increasing the stiffness of the carbon cloth, thus saving costs.

[0028] Example 1: The preparation method of composite carbon cloth electrode includes: 1) Pre-oxidized carbon fiber and metal wire were selected as raw materials, wherein: the pre-oxidized carbon fiber was polyacrylonitrile-based (PAN) carbon fiber with a diameter of 12 μm, an oxygen content of 8%, and a breaking elongation of 15%; the metal wire was titanium wire with a diameter of 80 μm; PAN-based carbon fibers are twisted into pure carbon fiber yarn; and PAN-based carbon fibers and titanium wires are twisted into a blended yarn with a specific monofilament content, wherein: Pure carbon fiber yarn is made by twisting 80 carbon fiber monofilaments together. The blended yarn is made of 80 carbon fiber monofilaments and 8 titanium wires twisted together; When twisting, the twist rate is 300 twists / meter and the twist direction is Z twist; 2) Produce carbon fiber cloth with a width of 20cm, a length of 50cm, and a thickness of 0.8mm on a loom. The longitudinal direction uses a mixed yarn of pre-oxidized carbon fiber and metal wire obtained by twisting, and the transverse direction uses pure carbon fiber yarn obtained by twisting. In this step, the fabric on the machine is woven with single strands of yarn; and the weave texture is plain; the warp and weft density is 15 warp threads / cm and 15 weft threads / cm; the fabric is a single layer. 3) The obtained carbon fiber cloth was placed in a sealed carbonization furnace and heated to 1150℃ under inert gas protection, and kept at a constant temperature for 3 hours for carbonization. 4) Cool down and remove the carbonized carbon cloth. Soak it in deionized water and boiling water three times, 30 minutes each time, to remove surface tar impurities. Dry it with nitrogen hot air at 100℃ for 2 hours. 5) In an air atmosphere, treat the surface of the carbon cloth obtained above with 300W plasma for 8 minutes to form oxygen-containing functional groups such as -COOH and -OH on the surface of the carbon cloth electrode. 6) The plasma-treated carbon cloth electrode was immersed in a dilute sulfuric acid solution (concentration of 0.5 mol / L) at room temperature for 2 hours, washed with deionized water until neutral, and dried by nitrogen purging to obtain a supportive composite carbon cloth electrode.

[0029] Example 2: The preparation method of composite carbon cloth electrode includes: 1) Pre-oxidized carbon fiber and metal wire were selected as raw materials, wherein: the pre-oxidized carbon fiber was polyacrylonitrile-based (PAN) carbon fiber with a diameter of 12 μm, an oxygen content controlled at 8%, and a breaking elongation of 15%; the metal wire was titanium wire with a diameter of 80 μm; PAN-based carbon fibers are twisted into pure carbon fiber yarn; and PAN-based carbon fibers and titanium wires are twisted into yarn with a specific monofilament content, wherein: Pure carbon fiber yarn is made by twisting 80 carbon fiber monofilaments together. The blended yarn is made of 80 carbon fiber monofilaments and 8 titanium wires twisted together; When twisting, the twist rate is 300 twists / meter and the twist direction is Z twist; 2) Produce carbon fiber cloth with a width of 20cm, a length of 50cm, and a thickness of 0.8mm on a loom. The transverse direction uses a mixed yarn of pre-oxidized carbon fiber and metal wire obtained by twisting, and the longitudinal direction uses pure carbon fiber yarn obtained by twisting. In this step, the fabric on the machine is woven with single strands of yarn; and the weave texture is plain; the warp and weft density is 15 warp threads / cm and 15 weft threads / cm; the fabric is a single layer. 3) The obtained carbon fiber cloth was placed in a sealed carbonization furnace and heated to 1150℃ under inert gas protection, and kept at a constant temperature for 3 hours for carbonization. 4) Cool down and remove the carbonized carbon cloth. Soak it in deionized water and boiling water three times, 30 minutes each time, to remove surface tar impurities. Dry it with nitrogen hot air at 100℃ for 2 hours. 5) In an air atmosphere, treat the surface of the carbon cloth obtained above with 300W plasma for 8 minutes to form oxygen-containing functional groups such as -COOH and -OH on the surface of the carbon cloth electrode. 6) The plasma-treated carbon cloth electrode was immersed in a dilute sulfuric acid solution (concentration of 0.5 mol / L) at room temperature for 2 hours, washed with deionized water until neutral, and dried by nitrogen purging to obtain a supportive composite carbon cloth electrode.

[0030] Example 3: The preparation method of composite carbon cloth electrode includes: 1) Pre-oxidized carbon fiber and metal wire were selected as raw materials, wherein: the pre-oxidized carbon fiber was polyacrylonitrile-based (PAN) carbon fiber with a diameter of 12 μm, an oxygen content controlled at 8%, and a breaking elongation of 15%; the metal wire was titanium wire with a diameter of 80 μm; PAN carbon fibers are twisted into pure carbon fiber yarn; and PAN-based carbon fibers and titanium wires are twisted into yarn with a specific monofilament content, wherein: Pure carbon fiber yarn is made by twisting 80 carbon fiber monofilaments together. The blended yarn is made of 80 carbon fiber monofilaments and 8 titanium wires twisted together; When twisting, the twist rate is 300 twists / meter and the twist direction is Z twist; 2) Produce carbon fiber cloth with a width of 20cm, a length of 50cm, and a thickness of 0.8mm on a loom. The cloth is made of a mixture of pre-oxidized carbon fiber and metal wire obtained by twisting in both the transverse and longitudinal directions. In this step, the fabric on the machine is woven with single strands of yarn; and the weave texture is plain; the warp and weft density is 15 warp threads / cm and 15 weft threads / cm; the fabric is a single layer. 3) The obtained carbon fiber cloth was placed in a sealed carbonization furnace and heated to 1150℃ under inert gas protection, and kept at a constant temperature for 3 hours for carbonization. 4) Cool down and remove the carbonized carbon cloth. Soak it in deionized water and boiling water three times, 30 minutes each time, to remove surface tar impurities. Dry it with nitrogen hot air at 100℃ for 2 hours. 5) In an air atmosphere, treat the surface of the carbon cloth obtained above with 300W plasma for 8 minutes to form oxygen-containing functional groups such as -COOH and -OH on the surface of the carbon cloth electrode. 6) The plasma-treated carbon cloth electrode was immersed in a dilute sulfuric acid solution (concentration of 0.5 mol / L) at room temperature for 2 hours, washed with deionized water until neutral, and dried by nitrogen purging to obtain a supportive composite carbon cloth electrode.

[0031] Comparative Example 1 (Uncomposite Metal Wire): Methods for preparing carbon cloth electrodes include: 1) Pre-oxidized carbon fiber was selected as the raw material, wherein: the pre-oxidized carbon fiber was PAN-based carbon fiber with a diameter of 12 μm, an oxygen content controlled at 8%, and an elongation at break of 15%; PAN-based carbon fiber is twisted into pure carbon fiber yarn, which is made of 80 carbon fiber monofilaments twisted together. When twisting, the twist rate is 300 twists / meter and the twist direction is Z twist; 2) Produce carbon fiber cloth with a width of 20cm, a length of 50cm, and a thickness of 0.8mm on a loom, wherein pure carbon fiber yarn obtained by twisting is used in both the transverse and longitudinal directions. In this step, the fabric on the machine is woven with single strands of yarn; and the weave texture is plain; the warp and weft density is 15 warp threads / cm and 15 weft threads / cm; the fabric is a single layer. 3) The obtained carbon fiber cloth was placed in a sealed carbonization furnace and heated to 1150℃ under inert gas protection, and kept at a constant temperature for 3 hours for carbonization. 4) Cool down and remove the carbonized carbon cloth. Soak it in deionized water and boiling water three times, 30 minutes each time, to remove surface tar impurities. Dry it with nitrogen hot air at 100℃ for 2 hours. 5) In an air atmosphere, treat the surface of the carbon cloth obtained above with 300W plasma for 8 minutes to form oxygen-containing functional groups such as -COOH and -OH on the surface of the carbon cloth electrode. 6) After plasma treatment, the carbon cloth electrode is immersed in dilute sulfuric acid solution (concentration of 0.5 mol / L) at room temperature for 2 hours, washed with deionized water until neutral, and then purged with nitrogen to dry.

[0032] Comparative Example 2 (the amount of carbon fiber and metal wire is not covered by this application): The preparation method of composite carbon cloth electrode includes: Step 1) is performed in accordance with Example 1, except that the selected PAN-based carbon fiber is twisted into pure carbon fiber yarn; and the selected PAN-based carbon fiber and titanium wire are twisted into yarn with a specific monofilament content, wherein: In pure carbon fiber yarn, there are 6 carbon fiber monofilaments; In the blended yarn, the ratio of pre-oxidized carbon fiber monofilaments to metal wires is 1:1. The remaining steps are the same as in Example 1.

[0033] Test example: The carbon cloth electrodes prepared in the above embodiments and comparative examples are applied to the assembly of flow batteries. The specific steps are as follows: The flow battery components are stacked and assembled in the following order: current collector - flow channel bipolar plate - electrode - separator - electrode - flow channel bipolar plate - current collector. The electrode active area is 28 cm². 2 The assembly pressure is 2 MPa.

[0034] Then, the assembled battery was subjected to performance testing: with 1.7 mol / L vanadium electrolyte, the battery was tested at 160 mA / cm². 2 Battery efficiency under constant current charge and discharge conditions.

[0035] The test results are shown in Table 1 below.

[0036] Table 1 Battery performance test results

[0037] This application improves the rigidity of the composite carbon cloth electrode material by adding metal wires during the weaving process of carbon fiber cloth. When assembling the flow battery stack, the carbon cloth is less likely to collapse into the bipolar plate channel, so that the carbon cloth electrode can make uniform contact with the membrane, thereby improving the energy efficiency of the flow battery.

[0038] In Comparative Example 1, no metal wires were added during the weaving process of carbon fiber cloth. The carbon cloth electrode material was too soft and easily collapsed to the bottom of the flow channel, thus losing contact with the membrane and resulting in poor battery performance.

[0039] In Comparative Example 2, the ratio of carbon fiber to metal wire was not controlled within a suitable range when metal wire was added during the weaving process of carbon fiber cloth. If the proportion of metal wire was too high, too many metal wires would crowd out the reaction sites of carbon fiber, reduce the catalytic activity of the electrode, and cause the polarization of the battery charge and discharge to increase significantly, resulting in a significant decrease in energy efficiency.

[0040] Although the present invention has been described in detail through the preferred embodiments described above, it should be understood that the above description should not be considered as a limitation of the present invention. Those skilled in the art will understand that modifications or adjustments can be made to the present invention based on the teachings of this specification. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a composite carbon cloth electrode suitable for flow batteries, characterized in that, include: (1) Twist the pre-oxidized carbon fiber to obtain twisted pure carbon fiber yarn; Pre-oxidized carbon fiber and metal wire are twisted to obtain twisted mixed yarn; (2) Make carbon fiber cloth on a loom, wherein the mixed yarn twisted in step (1) is used in the longitudinal direction and the pure carbon fiber yarn twisted in step (1) is used in the transverse direction; or, the mixed yarn twisted in step (1) is used in the transverse direction and the pure carbon fiber yarn twisted in step (1) is used in the longitudinal direction; or, the mixed yarn twisted in step (1) is used in both the longitudinal and transverse directions. (3) Carbonize the carbon fiber cloth obtained in step (2) to obtain carbonized carbon cloth. (4) The carbon cloth surface obtained above is subjected to plasma treatment to obtain a surface-modified carbon cloth electrode; (5) The plasma-treated carbon cloth electrode is immersed in acid solution to obtain a composite carbon cloth electrode.

2. The preparation method according to claim 1, characterized in that, The pre-oxidized carbon fiber is selected from one or more of polyacrylonitrile-based carbon fiber, viscose-based carbon fiber, and pitch-based carbon fiber; The diameter of the pre-oxidized carbon fiber is 5~20μm.

3. The preparation method according to claim 1, characterized in that, The metal wire is selected from one or more of copper wire, iron wire, platinum wire, titanium wire, tungsten wire, and iridium wire; The diameter of the metal wire is 5~200μm.

4. The preparation method according to claim 1, characterized in that, In the twisted pure carbon fiber yarn, the number of pre-oxidized carbon fiber monofilaments is 10 to 200. In the twisted blended yarn, the ratio of the number of pre-oxidized carbon fiber monofilaments to the number of metal wires is 8:1 to 12:1, preferably 10:

1.

5. The preparation method according to claim 1, characterized in that, The carbonization process conditions in step (3) include: under inert gas protection, the system is heated to 500~1400℃ for carbonization treatment, and the treatment time is 2~4h.

6. The preparation method according to claim 1, characterized in that, Prior to plasma treatment, the carbonized carbon cloth is washed and dried.

7. The preparation method according to claim 1, characterized in that, The process conditions for plasma treatment in step (4) include: treating the surface of carbon cloth with 200-500W plasma in an air atmosphere for 5-30 minutes.

8. The preparation method according to any one of claims 1-7, characterized in that, Step (5) The process of soaking in acid solution includes: soaking in dilute acid solution at room temperature for 1 to 24 hours, washing with water until neutral, purging with nitrogen and drying to obtain composite carbon cloth electrode; Preferably, the dilute acid solution is a dilute sulfuric acid solution with a concentration of 0.1~0.5 mol / L.

9. The composite carbon cloth electrode prepared by any one of claims 1-8.

10. The application of the composite carbon cloth electrode prepared by any one of claims 1-8 in a flow battery.

Citation Information

Patent Citations

  • Preparation method for polyacrylonitrile-based carbon cloth

    CN102704227A